ANALISIS DESAIN PEMASANGAN PLTS ON-GRID DI GBTE UNIVERSITAS BRAWIJAYA: STUDI KELAYAKAN PADA ASPEK TEKNIK DAN EKONOMI - Adrian Adam Indrabayu; Rini Nur Hasanah; Lunde Ardhenta (Jurnal Mahasiswa TEUB, 2023)
Solar energy is energy that comes from the sun and has great potential to be utilized, one of which is to make electricity. In line with the target of a 23% renewable energy mix in Indonesia through the National Energy General Plan (RUEN), solar energy is one of the main renewable energies to be developed through solar panels. This is intended as one of the efforts to reduce Green House Gas (GHG) emissions, achieve energy independence in the future, and form an energy source at an affordable cost. The Electrical Engineering Joint Building of Brawijaya University (GBTE UB) is one of the buildings in the UB campus which will be the object of research in this study. The purpose of this study is to determine the feasibility of installing an on-grid rooftop Solar Power Plant (PLTS). This study was conducted by reviewing the feasibility of installation from two aspects, namely technical and economic aspects. There is several software needed in this study which include: Helioscope, PVSyst 7.2, and ETAP. Helioscope and PVSyst 7.2 are useful in determining the correct type of components and simulating various types of plotting available. Based on the simulation, it was found that 46 Trina Solar TSM-PE14A 320 Wp modules and an inverter with a capacity of 12 kW would give a Performance Ratio (PR) value of 80.7% and a DC/AC ratio of 1.23. The total power produced by PV system is 14,72 kWp and energy produced is more than 18 MWh annually will be supplied to the load at GBTE UB. ETAP 16.0 is used to determine the power distribution in the system. It is noted that the load at GBTE UB uses 15,1 kVA and still needs 8,14 kVA power supply from PLN. Economically, the initial investment required to install a PLTS on-grid is IDR 208,619,628 with a net metering scheme of 1:1. Therefore by this scheme, all surplus energy produced by the PV system might be able to be exported to PLN grid 100%. The simulation shows that the NPV is 256.265.384 IDR, IRR is 19%, PP is 6,45 tahun, and PI is 31,04. Based on the feasibility study, the PLTS system was successfully assessed as feasible to implement as an effort to accelerate renewable energy in Indonesia. Keywords: solar power plant, on-grid, Helioscope, PVSyst 7.2, Economic